1994
DOI: 10.1172/jci117544
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic factor significantly contributes to the mineralocorticoid escape phenomenon. Evidence for a guanylate cyclase-mediated pathway.

Abstract: The mechanism underlying the mineralocorticoid escape phenomenon remains unknown. To assess the possible contribution of natriuretic peptides to mineralocorticoid escape, rats were injected with 5 mg deoxycorticosterone acetate for 3 d. Plasma atrial natriuretic factor (ANF) rose to twice basal levels and atrial ANF content decreased significantly by 24 h of treatment. This coincided with renal escape and with a significant increase in urinary cGMP excretion. Plasma ANF remained elevated and atrial ANF content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 63 publications
2
27
0
Order By: Relevance
“…In addition, intravascular volume expansion may also increase renal interstitial hydrostatic pressure with reductions in peritubular Starling forces at the level of the proximal tubule to reduce proximal reabsorption of sodium. 26 Other studies investigating mineralocorticoid escape have found roles for natriuretic peptides, [27][28][29][30] NO, 31 and the thiazide-sensitive sodium chloride cotransporter. 32 Titze et al 33 reported that administration of DOCA and salt to rats was associated with osmotically inactive sodium storage and osmotically neutral sodium retention balanced by potassium loss.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intravascular volume expansion may also increase renal interstitial hydrostatic pressure with reductions in peritubular Starling forces at the level of the proximal tubule to reduce proximal reabsorption of sodium. 26 Other studies investigating mineralocorticoid escape have found roles for natriuretic peptides, [27][28][29][30] NO, 31 and the thiazide-sensitive sodium chloride cotransporter. 32 Titze et al 33 reported that administration of DOCA and salt to rats was associated with osmotically inactive sodium storage and osmotically neutral sodium retention balanced by potassium loss.…”
Section: Discussionmentioning
confidence: 99%
“…The 'escape' is the result of compensatory suppressed Na resorption in nephron segments proximal to the collectin ducts (2,14). There is evidence that Arial natriuretic peptide (ANP) plays an important role in mineralocorticoid escape (30,33). The mechanisms responsible for an increase in mipheral resistance and the associated hypertension are unclear (10).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experimental work 2,30 suggests that ANF plasma levels may be a measure of extracellular volume status whereas BNP levels reflect cardiac hypertrophy and ventricular dysfunction. 31,32 These underlying events, superimposed to the specific effect(s) of the inflammatory process and together with varying degrees of the preservation of renal function in individual patients, may explain the variations in NP ratios that were found.…”
Section: Masters Et Al Natriuretic Peptides In Cardiac Transplantatiomentioning
confidence: 99%